Heat Transport in Double-Bond Linear Chains of Fullerenes*Supported by the National Natural Science Foundation of China under Grant Nos 11004082 and 11005048, and the Natural Science Foundation of Guangdong Province under Grant No 2014A030313367. (July 2015) - Wei, Liang; Xu, Zhi-Cheng; Zheng, Dong-Qin; Zhang, Wei; Zhong, Wei-Rong
<x content-type="archive" xml:space="preserve">Abstract</x> Heat transport in one kind of double-bond linear chains of fullerenes (C60's) is investigated by the classical nonequilibrium molecular dynamics method. It is found that the negative differential thermal resistance (NDTR) is more likely to occur at larger temperature difference and shorter length. In addition, with the increase of the length, the thermal conductivity of the chains increases, and NDTR region shrinks and vanishes in the end. The temperature profiles reveal that a large temperature jump exists at a high-temperature boundary of the chains when NDTR occurs. These results may be helpful for designing thermal devices where low-dimensional C60 polymers can be used.